Sistem Aplikasi Coding Dan Indexing Pasien Rawat Jalan Di Puskesmas Bringkoning Madura - Wincoko, Wincoko; Mahmud, Muhamad; Kurniasari, Iin (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2022)
The problems faced at Bringkoning Madura Community Health Center are the coding and indexing system for outpatients, which are not computerized at this time. In all recording systems, it is still manual using notebooks where there are several shortcomings. According to the results of observations that have been made, the shortcomings include that it takes a long time and the data is inaccurate. One of the contributing factors is the inaccuracy at the time of writing in seeing the number of outpatients. The purpose of this study is to create an outpatient coding and indexing application using the programming language PHP and MySQL. The method used is using the waterfall model with the programming languages PHP and MySQL. This type of research This research uses the type of development research (Research and Development). Based on the results of the research, this application makes it easy for medical record officers, doctors, and officers in charge of anticipating actions to be taken on outpatients because they can be accessed wherever they are.